2018
DOI: 10.1080/20008198.2018.1487225
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an intensive treatment programme combining prolonged exposure and eye movement desensitization and reprocessing for severe post-traumatic stress disorder

Abstract: Background: There is room for improvement regarding the treatment of severe post-traumatic stress disorder (PTSD). Intensifying treatment to increase patient retention is a promising development. Objective: The aim of this study was to determine the effectiveness of an intensive trauma-focused treatment programme over 8 days for individuals suffering from severe PTSD. Method: Treatment was provided for 347 PTSD patients (70% women; mean age = 38.32 years, SD = 11.69) and consisted of daily sessions of prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 40 publications
8
86
1
Order By: Relevance
“…Since 2010, we have seen innovations in the modes of treatment delivery, which have increased patient choice and access to treatment. For example, we have learned that trauma-focused psychological treatments can be safely and effectively delivered in an intensive format (Ehlers et al, 2014;Hendriks, de Kleie, Broekman, Hendriks, & van Minnen, 2018;Méndez, Nijdam, June Ter Heide, van der Aa, & Olff, 2018;Van Woudenberg et al, 2018). We have also seen that therapist input can be shortened through the use of self-study modules (Wild & Ehlers, 2010) and that rotation of therapists is feasible (Van Minnen et al, 2018).…”
Section: Psychological Treatment Development and Deliverymentioning
confidence: 99%
“…Since 2010, we have seen innovations in the modes of treatment delivery, which have increased patient choice and access to treatment. For example, we have learned that trauma-focused psychological treatments can be safely and effectively delivered in an intensive format (Ehlers et al, 2014;Hendriks, de Kleie, Broekman, Hendriks, & van Minnen, 2018;Méndez, Nijdam, June Ter Heide, van der Aa, & Olff, 2018;Van Woudenberg et al, 2018). We have also seen that therapist input can be shortened through the use of self-study modules (Wild & Ehlers, 2010) and that rotation of therapists is feasible (Van Minnen et al, 2018).…”
Section: Psychological Treatment Development and Deliverymentioning
confidence: 99%
“…In accordance with these positive results, new intensive trauma-focused treatments have been developed that incorporate physical activity together with PE and EMDR therapies. These treatments have shown low dropout rates and strong reductions in PTSD symptoms within a short time frame of 5 to 8 treatment days (Van Woudenberg et al, 2018;Zepeda Méndez, Nijdam, Ter Heide, Van Der, & Olff, 2018). However, the relation between physical activity and PTSD treatment outcome is not yet clear.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of another psychiatric condition concurrent with PTSD is not rare [33][34][35][36] . In our study, the rate of presence of comorbid psychiatric disease was found to be significantly higher in participants with a positive PTSD screen than in those with a negative PTSD screen; however, this was not found to be a risk factor for PTSD.…”
Section: Discussionmentioning
confidence: 99%